A study of the internal audit committee in the co-operative movement in Malaysia - Kaur, Indar; Nurizah Noordin; Noor Zeeta Mohd. Ramli; Zulkiflee Aspan (Research monograph, 2008)
The objectives of this research is to studyy the extent to which the IAC in co-operatives is functioning in compliance with provisions of the co-operative legislation. More specifically this study aims to provide an insight into the IAC's demographic profile, their level of knowledge of the IAC'a functions, their experience, attendance of mandatory training and current audit practices including frequency of audit and submission of audit reports